Synthesis and Antimalarial evaluation of Gold Thiosemicarbazone Complexes and Polyamine-Thiosemicarbazone Dendrimers - Khanye, Setshaba David (Department of Chemistry, 2014)
Malaria still remains one of the most dangerous widespread parasitic diseases in developing nations. Reported alarming figures of malaria infections annually highlight the âgapâ that remains to be filled to rid endemic of malaria. As cases of increasing spread of malaria and the emergence of resistance continue to exert pressure on health systems in most affected areas, novel antimalarial compounds are endlessly needed to overcome the problem of malaria infections. This thesis presents research investigating a series of thiosemicarbazones (TSCs) and their novel gold complexes and dendrimers as potential antimalarial agents. A series of TSCs were synthesised in one step using Schiff base chemistry. On the other hand pyrazoline analogues were obtained in two steps using both Mannich and Schiff base chemistries. A range of gold(I) TSC complexes were achieved by reacting TSCs with the starting gold(I) materials, [AuI(PEt3P)Cl] (4.2), [AuI(THT)Cl] (4.3), [AuI(Ph3P)Cl] (4.5), [AuI(PTA)Cl] (4.24), and C6F5AuI(THT) (4.34). Further reaction of TSCs with starting gold(III) complex 2.15 yielded the corresponding series of gold(III) TSC complexes. All the compounds were characterised by multinuclear NMR and FT-IR spectroscopies, mass spectrometry and elemental analysis. Gold(I) complexes 4.15 and 4.16 were further characterised by single X-ray crystallography. The synthesised ligands and complexes were tested for their antiplasmodial activity against chloroquine-sensitive (D10, 3D7) and chloroquine-resistant (W2, K1) strains of the malaria parasite Plasmodium falciparum. These compounds were also evaluated for inhibitory activity against the malarial cysteine protease (falcipain-2). In most cases gold complexes showed enhanced antiplasmodial activities relative to their corresponding ligands. However, no correlation was found between antiplasmodial activities and the inhibition of falcipain-2 in respect of studied compounds. Reaction of TSC thioesters 6.23 with branched dendritic polyamines (PAs) led to two series of polyamine-TSC dendrimers 6.24 and 6.25 whose chemical structures were elucidated using a range of techniques. Similarly, these dendritic TSCs were also tested for their antiplasmodial activity against the W2 strain. Generally, this class of compounds displayed improved antiplasmodial activities in the mid to low micromolar range. The most active compounds were 6.24c (IC50 = 0.79 ïM) and 6.24d (IC50 = 0.67 ïM), respectively.